Linking variability in soil solution dissolved organic carbon to climate, soil type, and vegetation type. Issue 5 (2nd May 2014) - Camino‐Serrano, Marta; Gielen, Bert; Luyssaert, Sebastiaan; Ciais, Philippe; Vicca, Sara; Guenet, Bertrand; Vos, Bruno De; Cools, Nathalie; Ahrens, Bernhard; Altaf Arain, M.; Borken, Werner; Clarke, Nicholas; et al.
Abstract Lateral transport of carbon plays an important role in linking the carbon cycles of terrestrial and aquatic ecosystems. There is, however, a lack of information on the factors controlling one of the main C sources of this lateral flux, i.e., the concentration of dissolved organic carbon (DOC) in soil solution across large spatial scales and under different soil, vegetation, and climate conditions. We compiled a database on DOC in soil solution down to 80 cm and analyzed it with the aim, first, to quantify the differences in DOC concentrations among terrestrial ecosystems, climate zones, soil, and vegetation types at global scale and second, to identify potential determinants of the site‐to‐site variability of DOC concentration in soil solution across European broadleaved and coniferous forests. We found that DOC concentrations were 75% lower in mineral than in organic soil, and temperate sites showed higher DOC concentrations than boreal and tropical sites. The majority of the variation (R2 = 0.67–0.99) in DOC concentrations in mineral European forest soils correlates with NH4+, C/N, Al, and Fe as the most important predictors. Overall, our results show that the magnitude (23% lower in broadleaved than in coniferous forests) and the controlling factors of DOC in soil solution differ between forest types, with site productivity being more important in broadleaved forests and water balance in coniferous stands.